Persistently elevated intracranial pressure in cryptococcal meningitis– 76 therapeutic lumbar punctures - Jjunju, Samuel; Nuwagira, Edwin; Meya, David B.; Muzoora, Conrad (Medical Mycology Case Reports, 2023)
Cryptococcal meningitis still remains the most common form of adult meningitis in sub-Saharan Africa, due to the burden of HIV/AIDS. Increased intracranial pressure (ICP) is a major complication of cryptococcosis and requires aggressive management with therapeutic lumbar punctures (LPs). In this report, we describe a patient with persistently elevated ICP who underwent 76 LPs over 46 days with good outcome. While unusual, this highlights the importance of serial therapeutic LPs.
Keywords: Cryptococcal meningitis; Increased intracranial pressure; Lumbar puncture; Human Immunodeficiency Virus